KEMUNGKINAN PENGGUNAAN BAHAN PENGAWET ZFK - Sasa Abdurrohim; Pipin Permadi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
Since CCA preservative was banned in Indonesia, alternative preservative should be searched. One of the preservative which has good fixation characteristic like CCA is ZFE. preservative that contain zink, fluor and chrom.The retention and penetration of ZFK in five Indonesian wood species were studied. The ZFK preservative was applied using soaking method for 3, 5 and 7 days, where the solution concentration applied was 5 % and 10%. Five wood species choosed in the experiment were damar (Agathis loranthifolia), keruing (Dipterocarpus caudiferus), jelutung (Dyera costulata), meranti merah (Shorea palembanica) and nyatoh (Palaquium leiocarpum).The lest results based on retention and penetration requirements for wood used under roof, and in the open air both without ground contact, showed that only two species, keruing and jelutung, could satisfactorily meet the standard under the experimental conditions, while other tree species (damar, meranti merah and nyatoh) do not comply with tire standard. For under roof and in the open air uses without ground contact keruing can be consecutively soaked for 7 days in Basilit ZFK solution of 10% , while jelutung for 5 days.